Scoping Studies into the Structure-Activity Relationship (SAR) of Phenylephrine-Derived Analogues as Inhibitors of Trypanosoma brucei rhodesiense - Cullen, Danica; Pengon, J.; Rattanajak, R.; Chaplin, J.; Kamchonwongpaisan, S.; Mocerino, Mauro (Wiley - V C H Verlag GmbH & Co. KGaA, 2016)
Human African Trypanosomiasis (HAT) is a disease caused by the parasite Trypanosoma brucei and is classified as a neglected tropical disease of concern in sub-Saharan Africa. A scoping study has been undertaken to develop a preliminary structure activity relationship of a tetrahydroisoquinoline scaffold. Fourteen compounds based around this core scaffold were synthesised and evaluated for their activity against Trypanosoma brucei rhodesiense in vitro. Initial results are promising with a number of analogues showing low micromolar inhibition of T.b.rhodesiense with acceptable selectivity over mammalian cells. The most promising is a secondary amine analogue showing the most potent inhibition of T.b.rhodesiense, with an IC50 value of 0.25 ± 0.02 µM, while also showing low cytotoxicity to mammalian cells.